Optimization and greenness assessments of the supramolecular solvent-assisted cloud point extraction method for copper spectrophotometric determination in water and food samples - Ekhlas A. AbdulKareem; Azhar Y.M. Al-Murshedi; Rana Kadhim Ridha; Ebaa Adnan Azooz (Green Analytical Chemistry, 2024)
For the first time, the green supramolecular solvents (SUPRASs)-based cloud point extraction (CPE) approach was created for copper spectrophotometric determination in food and water samples. SUPRASs were synthesized in six different forms and used as synergistic reagents. SUPRAS (water, salicylic acid, and THF) mixed with TritonX-114 (TX-114) to be the most efficient extraction solvent. The validation investigation found that the linearity range, limit of detection (LOD), limit of quantification (LOQ), enhancement factor (EF), and preconcentration factor (PF) are 0.2-700.0 μg L-1, 0.1 μg L-1, 0.33 μg L-1, 85.0, and 50.0, respectively. The technique's accuracy was calculated using standard reference materials (SRMs) (GBW07605 Tea Leaves and GBW10019 Apple) and ranged between 96.0 and 98.9%. Lastly, a novel SUPRAS-CPE approach was utilized to determine copper concentrations in real water, food tests, and SRMs. Furthermore, the SUPRAS-CPE conforms to green chemistry principles by using less both time and energy than previous studies. Also, the greenness values were determined by three recent tools. The Analytical Greenness Metric for Sample Preparation (AGREEprep), Complex Modified GAPI (ComplexMoGAPI), and Sample Preparation Metric of Sustainability (SPMS) programs produced results of 0.79, 86.0, and 8.42, respectively. These results are strongly aligned with both green ideals and environmentally friendly practices. The finding increases the possibilities for using SUPRAS-CPE to extract additional mineral ions.